Samoa : 2007 Article IV Consultation; Staff Report; and Public Information Notice on the Executive Board Discussion for Samoa. (IMF Staff Country Reports; Country Report ;, 2007)
Samoa has achieved a major economic transformation over the last decade and a half. This 2007 Article IV Consultation highlights that real per capita GDP in Samoa has increased by more than 3 percent per year on average, and external public debt has fallen below 40 percent of GDP. The external position benefited from the rapid growth of remittances and tourism receipts. Executive Directors have congratulated the authorities on Samoa's impressive growth performance and economic transformation over the past decade, with Samoa now set to graduate from least developed country status.